Deep-blue emitters (CIEy ∼0.07) based on phenanthroimidazole: Remarkable substitution effects at the N1 position of imidazole on the excited states and electroluminescence properties. (December 2021) - Girase, Jaipal Devesing; Tagare, Jairam; Shahnawaz,; Nagar, Mangey Ram; Siddiqui, Iram; Jou, Jwo-Huei; Patel, Sabita; Vaidyanathan, Sivakumar
Abstract: Organic light emitting diodes (OLEDs) has shown great potential (light weight, fast response time, flexible and energy efficient) and emerging technology for next-generation display and lighting application. In any case, achieving efficient blue electroluminescence still remains a challenge. Herein, two new deep blue phenanthroimidazole (A) and triphenylamine (D) based fluorophores, N, N -diphenyl-4'-(1-(p-tolyl)- 1H -phenanthro [9, 10-d]imidazole-2-yl)-[1, 1′-biphenyl]-4-amine (4-PIPTPA ) and N, N -diphenyl-4'-(1-(4-(trifluoromethyl)phenyl)- 1H -phenanthro [9, 10-d]imidazole-2-yl)-[1, 1′-biphenyl]-4-amine (4-PIPCFTPA) were designed and synthesized. The fluorophores were structurally characterized by spectroscopic methods. These fluorophores are tharmally stable with thermal decomposition temperature (Td ) of ∼446 °C. The photophysical, electronic (theoretical), electrochemical (CV), and electroluminescene properties were thoroughly investigated, the N1 substituted moieties are play a vital role as it affects the photophysical as well as electronic properties of the synthesized fluorophores. Hence, we fabricated undoped and doped devices with newly synthesized emitters and observed that the 4-PIPCFTPA demonstrated the superior performance as compared to that of 4-PIPTPA . The best electroluminescence performance is displayed by the device fabricated with 4-PIPCFTPA (1 wt% in the CBP host) and (3 wt% in the CBP host) with a maximum external quantum efficiency (EQE) of 2.7 and 2.9%, respectively and CIE coordinates of (0.17, 0.07) and (0.18, 0.12) were observed, respectively. The observed EL properties of emitters reveal its potential as efficient deep blue emitters for display applications. Graphical abstract: Image 1 Highlights: Two highly twisted deep-blue emitters based on TPA and phenanthroimidazole (D-π-A) moieties were designed and synthesized. The synthesized emitters showed high thermal stability and good photoluminescence quantum yields. HOMO and LUMO separation indicates fluorophores having good carrier transporting properties. Solution processed doped OLED based on 4-PIPCFTPA shown deep-blue EL (0.17, 0.07) close to NTSC standard with EQEmax of 2.7%.